Hard Times - Walter Hill; Felice, Orlandi; James Coburn; Jill Ireland; Margaret Blye; Michael McGuire; Strother Martin; Charles Bronson (USA Columbia Pictures Corporation, 1975)
In the depression, Chaney, a strong silent streetfighter, joins with Speed, a promoter of no-holds-barred street boxing bouts. They go to New Orleans where Speed borrows money to set up fights for Chaney, but Speed gambles away any winnings.
In the depression, Chaney, a strong silent streetfighter, joins with Speed, a promoter of no-holds-barred street boxing bouts...
Bryan Gindoff
Language(s): English
Subtitle(s): English
Keywords: Drama; Action